Newborn care practices and its determinants among postnatal mothers in Dessie Referral Hospital, Northeast Ethiopia - Yaregal Semanew (BMC Research Notes, 2019)
Abstract Objective Newborn care practices like the initiation of breastfeeding within an hour, delay baby bathing, cord cutting with a safe instrument, and thermal care is a crucial intervention for the avoidance of more than 75% of neonatal deaths. Therefore, this study aimed to describe the practices and determinants of newborn care among postnatal mothers attending postnatal clinics in Dessie Referral Hospital, Northeast Ethiopia. Results A total of 418 postnatal mothers included in the study. The finding indicated that the proportion of initiation of breastfeeding within an hour, baby bathing after 24 h, cord cutting with a safe instrument, and thermal care was 83.9%, 75.8%, 46.9%, and 80.8% respectively. Overall, 46.9% (95% CI 41.9, 51.9) of newborn care practices was good. In the multivariable logistic regression analysis; women earning 651–1400 Ethiopian birr monthly (AOR = 0.428; 95% CI 0.183, 0.999), women who delivered spontaneous vaginally for their recent delivery (AOR = 0.438; 95% CI 0.240, 0.800), and mothers who had antenatal follow up once (AOR = 0.111; 95% CI 0.013, 0.944) were factors significantly associated with newborn care practices. Therefore, enhancing antenatal care services and providing counseling for these spontaneously delivered mothers will increase newborn care practices.